2013
DOI: 10.1093/mp/sss103
|View full text |Cite
|
Sign up to set email alerts
|

AtPRK2 Promotes ROP1 Activation via RopGEFs in the Control of Polarized Pollen Tube Growth

Abstract: The ROP1 GTPase-based signaling network controls tip growth in Arabidopsis pollen tubes. Our previous studies imply that ROP1 might be directly activated by RopGEF1, which belongs to a plant-specific family of Rho guanine nucleotide exchange factors (RopGEFs) and in turn may be activated by an unknown factor through releasing RopGEF1's auto-inhibition. In this study, we found that RopGEF1 forms a complex with ROP1 and AtPRK2, a receptor-like protein kinase previously shown to interact with RopGEFs. AtPRK2 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
177
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(188 citation statements)
references
References 46 publications
9
177
1
1
Order By: Relevance
“…Several recent studies on the mechanism of pollen tube growth and ROS-mediated polarized root hair development showed that diverse RLKs can directly interact with and phosphorylate RopGEFs, and/or act upstream of ROPs. [30][31][32][33][34] A yeast two-hybrid screen showed that the tomato pollenspecific RLKs LePRK1 and LePRK2 interact with a tomato RopGEF homolog, which led to further work on a physical and functional interaction between the pollen-specific Arabidopsis RopGEF12 and a LePRK2 homolog AtPRK2a. 30,31 A series of biochemical and overexpression experiments suggest that this interaction recruits RopGEF12 to the plasma membrane and releases the inhibition of the C-terminal region on the GEF activity via PRK2a-mediated phosphorylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies on the mechanism of pollen tube growth and ROS-mediated polarized root hair development showed that diverse RLKs can directly interact with and phosphorylate RopGEFs, and/or act upstream of ROPs. [30][31][32][33][34] A yeast two-hybrid screen showed that the tomato pollenspecific RLKs LePRK1 and LePRK2 interact with a tomato RopGEF homolog, which led to further work on a physical and functional interaction between the pollen-specific Arabidopsis RopGEF12 and a LePRK2 homolog AtPRK2a. 30,31 A series of biochemical and overexpression experiments suggest that this interaction recruits RopGEF12 to the plasma membrane and releases the inhibition of the C-terminal region on the GEF activity via PRK2a-mediated phosphorylation.…”
mentioning
confidence: 99%
“…More recent work regarding AtPRK2 uncovers that this pollen-specific RLK regulate both RopGEF1 and ROP1 activities via forming a complex with them, which makes a conclusion that RopGEF1 bridges the signaling event from AtPRK2 to ROP1 to control polarized pollen tube growth in Arabidopsis. 34 Also, several members of the Catharanthusroseus RLK (CrRLK)-related family were identified as upstream regulators of RopGEFs. 32,35 CrRLK FERONIA (FER) acts as an upstream regulator of RAC/ROP2 signaling pathway most likely by interacting with RopGEF1.…”
mentioning
confidence: 99%
“…This finding confirms that the dissociated LePRK1 and LePRK2 both function during pollen tube growth within the pistil, possibly in response to different ligands. On the contrary, another aspect making the signaling pathway more complex is that PRKs share overlapping function as evidenced by the aggravated shortened pollen tubes in mutants depleted with multiple PRKs (Chang et al, 2012).…”
Section: Rlks Mediate Pollen Tube Growth In Pistilmentioning
confidence: 99%
“…In Arabidopsis, several members of PRK homologs also regulate pollen tube growth through RopGEF (Zhang and McCormick, 2007;Chang et al, 2012). Similar to the effect of excessive LePRK2 or KPP, over-expression of AtPRK2 or AtGEF causes ectopic GEF activity at a broad range on the plasma membrane of the tube tip, leading to pollen tube depolarization.…”
Section: Rlks Mediate Pollen Tube Growth In Pistilmentioning
confidence: 99%
See 1 more Smart Citation